Molecular Detection and Antimicrobial Resistance Pattern of Staphylococci Isolated from Clinical and Subclinical Bovine Mastitis - Jaiva, BB; Purohit, JH; Mathapati, BS; Barad, DB; Savsani, HS; Kalariya, VA; Patel, UD; Nimavat, VR (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
The present study was carried out on bovine mastitis with an objective to screen bovine milk samples around Junagadh for status of subclinical mastitis (SCM) by somatic cell count (SCC), to reveal the prevalence of staphylococcal mastitis by conventional and molecular methods and to evaluate the antimicrobial resistance pattern of the isolated Staphylococci. Total 390 bovine milk samples (180 from clinical mastitis and 210 from apparently healthy animals) were collected. Among 210 milk samples from healthy bovine, 72 samples showed SCC value > 5 lakhs/mL revealing 34.29% prevalence of SCM. A primary culture isolation of 252 milk samples (72 SCM and 180 clinical mastitis) showed 38.72% prevalence of Staphylococcal mastitis. The isolated Staphylococci were further characterized by biochemical tests which showed prevalence of coagulase negative Staphylococci and S. aureus 23.08% and 15.64%, respectively. The high resistance of Staphylococci was observed against ceftriaxone and amoxicillin-salbactum which displays antibiotic usage pattern in the region. Likewise bacterial isolates studied were highly sensitive to levofloxacin which suggest judicious use of this antibiotic in treatment of bovine mastitis. All the conventionally isolated Staphylococci and S. aurues were confirmed by polymerase chain reaction targeting 16S rRNA and nuc gene respectively in shorter period of time which signifies the superiority of molecular diagnostic tools.